I am Lost and Voiceless Contributor, The Challenges Encountered by Tourism Students of Higher Education in Collaborative Project - Kadek - Wiramarta (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2022)
In order to fulfill the industry's expanding demand for collaborative competencies, students in tourism vocational higher education programs must strengthen their social abilities. Teachers are particularly urged to use collaborative instructional strategy into their curriculum. Despite the numerous studies that emphasize the value of collaborative learning, there are only a few that emphasize the difficulty of collaborative learning, and even fewer that focus on tourism vocational students in higher education. Hence, this study has two objectives:  the perceptions of students and the challenges they face during collaborative learning projects. To collect the desired data, a survey and interpretive phenomenological analysis (IPA) were administered to 16 students who had participated in collaborative learning for 50% of their meetings this semester. This study indicated that there are divergent opinions on the implementation of the collaborative learning process, with some students believing that collaborative learning positively impacts their competency and others believing that it has no effect overall. Additionally, students pointed out their feel lost, voiceless and even struggling with the continuous effort when their peers have weak presence in the collaborative learning. This study is expected to shed lights on students’ negative emotional state while experiencing collaborative learning, which eventually help teacher to cope and overcome this issue. Keyword: Collaborative learning, higher education, tourism, vocational education and training,